Senter Faraday sebagai Proyek Inovasi dalam Pembelajaran Elektromagnetik Project Based Learning berbasis Science, Technology, Engineering, and Mathematic - Firda Ulya Nur Rosyidah; Parno Parno; Siti Zulaikah (Graduate School of Universitas Negeri Malang, 2020)
Abstract: Learning inovation needed to prepare the next generation to compety in twenty first century. Learning trend nowdays is integrating the ability of scientists and engineers to develop technology. One of goverment effort is determine basic competence. Students need understand the electromagnetic as basic technology development, espcially faraday induction in faraday flshlight. The aim of this paper to describe the gap between real condition, the characteristic of electromagnetic material and basic competence. This paper give solution by lesson plan. Data collected by survey. The result showed that electromagnetic learning still unreach the basic competence because less of engagement between students, learning media and time constraint. Students wish for the next learning can engage technology and project. Learning inovation which appropiate to solve this gap is project based learning (PjBL) based science, technology, engineering and mathematic (STEM).Abstrak: Inovasi pembelajaran dibutuhkan untuk mempersiapkan generasi siap saing di abad 21. Tren pembelajaran saat ini mengintegrasikan kemampuan saintis dan engineer dalam mengembangkan teknologi. Salah satu upaya pemerintah menentukan kompetensi dasar. Elektromagnetik sebagai basis perkembangan teknologi perlu dipahami siswa, salah satunya senter faraday. Artikel ini bertujuan mendeskripsikan kesenjangan antara kondisi nyata, karakteristik materi dan tuntutan KD. Disajikan inovasi solusi dalam bentuk rancangan pembelajaran. Data dikumpulkan melalui survei. Hasil penelitian menunjukkan pembelajaran elektromagnetik belum mencapai KD karena kurang melibatkan antar siswa maupun media pembelajaran dan kendala waktu. Siswa berharap pembelajaran melibatkan teknologi dan proyek. Inovasi pembelajaran yang sesuai adalah PjBL berbasis STEM.